The value of heparin-binding protein in bronchoalveolar lavage fluid in acute respiratory distress syndrome - Liu, Yang; Zhou, Wei; Xu, Wei; Lv, Xing-ping; Wang, Fei-fei; Wang, Xue-bin; Ma, Shao-lin (Frontiers in Medicine, 2025)
BackgroundHeparin-binding protein (HBP) is recognized as a significant factor in the development of Acute Respiratory Distress Syndrome (ARDS). Although plasma levels of HBP have been identified as a predictive biomarker for ARDS, the role and value of HBP in bronchoalveolar lavage fluid (BALF) remain unexplored.MethodsOur study utilized a cecum ligation and puncture (CLP) method to induce an ARDS model in mice, examining the correlations between plasma and BALF HBP levels, lung injury severity, lung wet-to-dry (WD) ratio, and BALF total protein levels. Additionally, we conducted a comparative analysis of BALF and plasma HBP levels in 44 ARDS patients and 38 patients with cardiogenic pulmonary edema (CPE), investigating their correlations.ResultsIn the animal study, CLP-induced mice demonstrated significantly higher lung WD ratios, BALF protein, BALF HBP, and plasma HBP levels compared to the control group. Notably, both BALF and plasma HBP levels were significantly correlated with lung injury severity. In human subjects, significant differences in BALF HBP, BALF protein, and plasma HBP levels were observed between ARDS and CPE patients, along with notable correlations between these markers and the severity of lung injury. Particularly, BALF HBP levels exhibited a stronger correlation with lung injury compared to plasma HBP levels.ConclusionThe study indicates that both BALF and plasma HBP levels are significantly elevated in the context of lung injury in both animal models and human ARDS patients. More importantly, BALF HBP levels show a stronger correlation with the severity of lung injury, suggesting that BALF HBP could serve as a valuable biomarker for diagnosing and guiding the treatment of ARDS.